2022
DOI: 10.1007/s11604-022-01322-w
|View full text |Cite
|
Sign up to set email alerts
|

Current status and challenges of percutaneous vertebroplasty (PVP)

Abstract: A narrative review regarding percutaneous vertebroplasty (PVP) for osteoporotic vertebral fracture (OVF) is provided herein, addressing the epidemic of OVF in Japan, the latest response to the criticism of PVP for OVFs, the indications and potential risks of PVP for OVFs, and a future perspective for PVP. Each year in Japan, approximately 32,000 patients aged 55 years or older suffer from chronic low back pain for several months to several years due to a compression fracture. PVP is one of the surgical treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…These cases were always on the borderline, where the patient was not suitable for a larger procedure, due to e.g., severe comorbidities. On the other hand, leaving some of those fracture untreated would most probably lead to severe deformity and persistent pain [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cases were always on the borderline, where the patient was not suitable for a larger procedure, due to e.g., severe comorbidities. On the other hand, leaving some of those fracture untreated would most probably lead to severe deformity and persistent pain [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent comparative analysis of kyphoplasty and vertebroplasty found significant differences in anatomical recovery with the former technique slightly superior in long‐term kyphotic correction and vertebral height restoration, 47 there is no valid quality evidence of balloon kyphoplasty versus vertebroplasty 20 . Moreover, cementoplasty practically improves quality of life and leads to higher levels of satisfaction, which may benefit from pain relief, a good relationship with the surgeon, and the patient's subjective perceptions 10 . Thus, a modified evaluation system for multicenter RCTs is warranted to assess the impact on quality of life and radiographic results.…”
Section: Discussionmentioning
confidence: 99%
“…As such, early mobilization and multisegmental treatment simultaneously are permitted, which is particularly applicable to fragile patients. 10 Previous studies also confirmed the clinical superiority of PVP/KP compared to conservative treatments, 11,12 while it must be acknowledged that PVP/KP have limitations. According to an evidenced-based review, 13 the symptomatic complication rates of PVP/KP of osteoporotic at 2.2%-3.9%.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In patients with vertebral compression fractures, nonoperative treatment is often difficult to tolerate. Both vertebroplasty and kyphoplasty are well-accepted minimally invasive procedures for the management of painful osteoporotic compression fractures [ 7 , 8 , 9 ]. Although adverse events are rare with both techniques, higher rates of procedure-related complications such as cement leakage were noted in vertebroplasty [ 10 ], and a higher incidence of an adjacent fracture was found after balloon kyphoplasty [ 11 ].…”
Section: Introductionmentioning
confidence: 99%